Edukasi Entrepreneur Fundamental Bagi Siswa SMA N 1 Petang - A. A. Gede Adi Mega Putra; A. A. Istri Ita Paramitha; I Gst. Agung Pramesti Dwi Putri; Ni Kadek Sri Mas Dwayani (I-Com: Indonesian Community Journal, 2024)
Amid current technological advancements, rapid economic growth through entrepreneurship presents opportunities for the younger generation. These skills should be taught in high school to prepare students for global challenges. The "Entrepreneur Fundamental" community service activity at SMA N 1 Petang aimed to provide an in-depth understanding of entrepreneurship to students. Conducted in April 2024 with 37 participants, the training covered four main topics, including the fundamental principles of ethics-based entrepreneurship. The results showed that students were inspired to develop an entrepreneurial spirit, motivated by young entrepreneurs' success stories, and able to identify business opportunities in their surroundings. Emphasizing business ethics aligned with local wisdom, such as Tri Hita Karana and Tattwam Asi, further strengthened their integrity and responsibility as future entrepreneurs. This activity successfully prepared students to face business world challenges. Given the substantial benefits, it is recommended to extend the training duration for more in-depth and comprehensive material.